TROPHIC SPECTRA AND RELATIONSHIP OF FISH SPECIES ASSEMBLAGES IN QUA IBOE RIVER, NIGER DELTA, NIGERIA - EKPO, I. E; UDO, M. T.; ODEN, E. (Nigerian Journal of Fisheries, 2014)
The trophic relationship of fish species in a coastal river in Akwa Ibom State were investigated to show trends in the feeding activity and condition factor from July – October 2008. 356 specimens were sampled from the Qua Iboe River which composed of 20 species, making it a total of 12 families and 20 genera. Feeding activity varied thus: GRI (16.65% in Thysochromis ansorgii – 100% in Xenomystus nigri, Isichthys henrgii, Anaspidoglanis akiri, Pelvicachromis pulcher and Polycentropsis abbreviata); AGR (1.31 in Barbus callipterus – 14.57 in A. akiri) and mean GSI (0.06% in Th. ansorgii – 7.09% in Epiplatys bifasciatus). Least mean value (K = 0.26) of condition factor was observed in I. henrgii while the highest (K = 2.06) was obtained in Tilapia mariae. The proportion of fish with food in the stomachs were higher (199; 55.90%) than stomachs without food (157; 44.10%) but were statistically insignificant (P > 0.05). The fishes were found to ingest a wide spectrum of materials ranging from microscopic to macroscopic organisms made up of 10 major food items. Thus, the fish species were classified into three broad trophic groups: herbivores, predators and detritivores. However, overlaps existed; they were found to feed on more than one type of food item which reduced competition.